Interdisciplinary Qualitative Research in Global Development: A Concise Guide - Haenssgen, Marco J. (Emerald Publishing Limited, 2019)
Interdisciplinary Qualitative Research in Global Developmentprovides a sorely needed practical introduction to the interdisciplinary and increasingly complex field of global development research, and it does so in a concise format can easily be taken into the field.